Implementacja prawa w ochronie przeciwpowodziowej = Implementation of law in flood protection - Hudak, Magda; Żebrowska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to the subject of the Water Framework Directive (WFD) in the context of the implementation of the provisions of the Polish legislation - resulting documents, legislation and public consultation. Equivalent to the WFD and fully consistent with the provisions of the Floods Directive.
Keywords: ochrona przeciwpowodziowa; prawo wodne; dyrektywa powodziowa; ramowa dyrektywa wodna; flood protection; polish legislation; Floods Directive